BPJS EMPLOYMENT DIGITAL TRANSFORMATION CHALLENGES AND OPTIMIZATION STRATEGIES - Umarsihad Said; Gede Sri Darma (SEAN Institute, 2022)
This research aimed at finding out the opportunities and challenges faced in the digital transformation at BPJS Ketenagakerjaan as well exploring the strategies that can be done to optimalize the digital transformation at BPJS Ketenagakerjaan in the new normal eral. This was a qualitative research in which the setting was the office of BPJS Ketenagakerjaan Bali Denpasar. The informants were gained through purposive sampling who were five staffs of BPJS Ketenagakerjaan Bali Denpasar. The data were collected through interviews and observation. The interviews were done by applying guided interview to get the detialed and depth answers about the research questions. The results showed that the challenges were not all the BPJS Ketenagakerjaan members were able to adapt to the digitalization. The internet connection was also a challenger in optimizing the digitalization faced by BPJS Ketenagakerjaan Bali Denpasar. The sharing information to the publich is a strategy that can be done to optimalizing the digitalization at BPJS Ketenagakerjaan Bali Denpasar.